2013
DOI: 10.1098/rspb.2012.2715
|View full text |Cite
|
Sign up to set email alerts
|

Shared and unique morphological responses of stream fishes to anthropogenic habitat alteration

Abstract: Understanding population-level responses to novel selective pressures can elucidate evolutionary consequences of human-altered habitats. Stream impoundments (reservoirs) alter riverine ecosystems worldwide, exposing stream fishes to uncommon selective pressures. Assessing phenotypic trait divergence in reservoir habitats will be a first step in identifying the potential evolutionary and ecological consequences of stream impoundments. We tested for body shape divergence in four stream-adapted fishes found in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
86
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 44 publications
7
86
1
1
Order By: Relevance
“…Circumstantial evidence for the role of stream velocity governing morphological evolution stems from studies on the effects of impoundments (dams), where water reservoirs reduce flow velocity and thus create artificial ‘downstream conditions’293031. Physical characteristics of reservoirs (i.e., altered flow characteristics) appear to drive changes in a set of morphological traits: fish are usually deeper-bodied and have smaller heads in reservoirs2931. This likely increases manoeuvrability when feeding on prey suspended in the water column, while more streamlined body contours increase locomotor performance in lotic environments32.…”
mentioning
confidence: 99%
“…Circumstantial evidence for the role of stream velocity governing morphological evolution stems from studies on the effects of impoundments (dams), where water reservoirs reduce flow velocity and thus create artificial ‘downstream conditions’293031. Physical characteristics of reservoirs (i.e., altered flow characteristics) appear to drive changes in a set of morphological traits: fish are usually deeper-bodied and have smaller heads in reservoirs2931. This likely increases manoeuvrability when feeding on prey suspended in the water column, while more streamlined body contours increase locomotor performance in lotic environments32.…”
mentioning
confidence: 99%
“…Common patterns of repeated ( parallel or convergent) evolution of the same performance-environment relationships emphasise the role that selection plays in generating among-taxa variation in locomotor performance, and in the physiological, morphological and behavioural traits that determine performance (Taylor and McPhail, 1985;McGuigan et al, 2003;Langerhans and DeWitt, 2004;Langerhans et al, 2006;Dalziel et al, 2012;Franssen et al, 2013;Fu et al, 2013;da Silva et al, 2014;Haas et al, 2015;Nelson et al, 2015). Despite the adaptive significance of locomotion, how the variation in locomotion is generated among individuals within a population, which is what natural selection acts upon, is relatively poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation among morphological traits is timedependent and displays high developmental plasticity (Grunbaum et al, 2007). It has been demonstrated that environmental factors such as current velocity, oxygen concentration, water temperature, and salinity may have a significant effect on fish morphotype (Mahon, 1984;Imre et al, 2002;Grunbaum et al, 2007;Paez et al, 2008;Crispo & Chapman, 2011;Franssen et al, 2012;Rajput et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fish morphology constitutes an important element of the phenotype, being largely defined by the lifestyle, locomotion activity, and habitat conditions (Webb, 1984;Guill et al, 2003;Franssen et al, 2012). Environmental factors can either directly influence body proportions or indirectly affect morphometric variation, when changes in one trait result in correlated changes in others (Crispo & Chapman, 2011).…”
Section: Introductionmentioning
confidence: 99%